Spatio-Temporal Analysis of STI Notifications in Brazilian Municipalities and the Effect of the COVID-19 Pandemic - Pereira, Bruna I. S.; Bezerra, Ana Luisa Lemos; Lavinscky, Anderson B. S.; Gir, Elucir; Cazzolato, Mirela T. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais Estendidos do XLI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd_estendido.2026.249646, 2026)
STI (Sexually Transmitted Infection) monitoring in Brazil has been an ongoing effort since the 1980s. With the establishment of DATASUS in 1991, it became possible to track annual variations in notifications across Brazilian municipalities. However, data from 2020 and 2021 reveal a significant drop in reported cases, coinciding with the COVID-19 pandemic. This study conducts a spatio-temporal analysis of STI notification time series covering Brazilian state capitals and neighboring municipalities, investigating whether this decline occurred in a systematic and geographically distributed manner. Experimental results uncover a consistent similarity pattern across states, pointing to a structural reduction in notifications during the pandemic period.